2022
DOI: 10.1177/21582440211071076
|View full text |Cite
|
Sign up to set email alerts
|

What are the Drivers of Profitability of Broiler Farms in the North-central and South-west Geo-political Zones of Nigeria?

Abstract: This study analyzed the drivers of the profitability of broiler farms in the north-central and south-west geo-political zones of Nigeria. A multi-stage sampling technique was employed to choose a representative sample. A pre-tested, structured questionnaire was employed to gather cross-sectional data from 645 respondents between November 2017 and February 2018 for 2017 production year by trained enumerators. The data were analyzed with budgetary model, descriptive and inferential statistics. The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Feed cost accounted for the majority (approximately 66.7%) of total variable cost in the study area of broiler farms. Our findings support the findings of Adeyonu and Odozi (2022) and Arslan et al, (2018), who stated that feed is the most expensive variable cost in broiler production. This was followed by the cost of day old birds (25.69%), with the remaining cost items (9%) being medication, transportation, hired and family labour, fuel cost, and other miscellaneous costs.…”
Section: Cost and Return On Broiler Production Per Farm And Cyclesupporting
confidence: 92%
See 1 more Smart Citation
“…Feed cost accounted for the majority (approximately 66.7%) of total variable cost in the study area of broiler farms. Our findings support the findings of Adeyonu and Odozi (2022) and Arslan et al, (2018), who stated that feed is the most expensive variable cost in broiler production. This was followed by the cost of day old birds (25.69%), with the remaining cost items (9%) being medication, transportation, hired and family labour, fuel cost, and other miscellaneous costs.…”
Section: Cost and Return On Broiler Production Per Farm And Cyclesupporting
confidence: 92%
“…The result further showed that the cost of producing a matured broiler bird was ₦1675.66, while ₦2521.44 was realized as income with profitability index of 45.53% implying that broiler farming is a profitable enterprise. The findings corroborate Khan and Afzal, (2018) and Adeyonu and Odozi's (2022) claims that livestock farms and other businesses can be successful, but at different rates depending on the farm.…”
Section: Cost and Return On Broiler Production Per Farm And Cyclesupporting
confidence: 81%
“…Furthermore, chicken mortality decreased with the farmer's experience in chicken production (years). More years of experience in chicken production enable the farmers to gain knowledge of different management practices that result in good health and high productivity [ 76 , 77 ]. Over time, they face different challenges and learn how to solve them by sharing with other farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Costs of production will be decreased by selecting the proper kind of feed. Farms who employed ready-made feed technology had higher profitability than their counterparts, who adopted self-made feed technology, according to Adeyonu and Odozi [8]. The quality of readymade feed may not be as challenging to achieve and maintain as the self-made feed that is intended to be more affordable [8].…”
Section: Broiler Feedmentioning
confidence: 99%
“…Furthermore, it plays an important role in reducing malnutrition, by providing the cheapest source of protein and promoting the nation's agricultural sector [7]. This is because broiler meat is the greatest white meat (other than rabbit, pork, and other poultry) consumed globally that has limited cultural and religious barriers, and is fairly low in fat and cheap compared to other meat products [8]. Poultry rearing offers a quick return on investment, especially for low-income smallscale farmers.…”
Section: Introductionmentioning
confidence: 99%